Modified vaginal lactobacilli expressing fluorescent and luminescent proteins for more effective monitoring of their release from nanofibers, safety and cell adhesion - Spase Stojanov; Tina Vida Plavec; Špela Zupančič; Aleš Berlec (Microbial Cell Factories)
Abstract Electrospun nanofibers offer a highly promising platform for the delivery of vaginal lactobacilli, providing an innovative approach to preventing and treating vaginal infections. To advance the application of nanofibers for the delivery of lactobacilli, tools for studying their safety and efficacy in vitro need to be established. In this study, fluorescent (mCherry and GFP) and luminescent (NanoLuc luciferase) proteins were expressed in three vaginal lactobacilli (Lactobacillus crispatus, Lactobacillus gasseri and Lactobacillus jensenii) and a control Lactiplantibacillus plantarum with the aim to use this technology for close tracking of lactobacilli release from nanofibers and their adhesion on epithelial cells. The recombinant proteins influenced the growth of the bacteria, but not their ability to produce hydrogen peroxide. Survival of lactobacilli in nanofibers immediately after electrospinning varied among species. Bacteria retained fluorescence upon incorporation into PEO nanofibers, which was vital for evaluation of their rapid release. In addition, fluorescent labelling facilitated efficient tracking of bacterial adhesion to Caco-2 epithelial cells, while luminescence provided important quantitative insights into bacterial attachment, which varied from 0.5 to 50% depending on the species. The four lactobacilli in dispersion or in nanofibers were not detrimental for the viability of Caco-2 cells, and did not demonstrate hemolytic activity highlighting the safety profiles of both bacteria and PEO nanofibers. To summarize, this study contributes to the development of a promising delivery system, tailored for local administration of safe vaginal lactobacilli.